Juridical Analysis of Motor Vehicle Financing Restructuring at PT. Adira Finance Medan After the Covid-19 Pandemic - Arie Syahwana; Elvira Fitriyani Pakpahan; Darwis Anatami (Lembaga Bale Literasi, 2025)
The financing restructuring policy serves as a strategic instrument for financial institutions to address problematic financing, including those experienced by PT Adira Finance in Medan. This policy is regulated under Bank Indonesia Regulation No. 10/18/PBI/2008, which outlines several restructuring mechanisms such as rescheduling, reconditioning, and restructuring. This study aims to examine the implementation of motor vehicle financing restructuring at PT Adira Finance Medan following the COVID-19 pandemic, to analyze the legal protection afforded to both debtors and creditors after the restructuring policy, and to explore the company’s approach to resolving non-performing loans (NPLs) arising from the pandemic, the enforcement of public activity restrictions (PPKM), and the transition to the new normal. This research employs a normative juridical approach, using qualitative and descriptive analysis based on literature studies and relevant legal documents. The findings indicate that PT Adira Finance Medan implemented a threefold restructuring strategy—rescheduling, reconditioning, and restructuring—to mitigate financial distress among customers. The policy proved effective in improving financing collectability and restoring customer financial stability. Furthermore, the legal protections ensured a balanced relationship between debtors and creditors, supporting financial resilience during and after the pandemic period. Overall, the restructuring initiative functioned as an adaptive and legally compliant solution for managing post-pandemic financing challenges.